Saint-Simonism and the Rationalisation of Industry - Mason, E. S. (Quarterly Journal of Economics, 1931)
I. Introduction, 640.—II. Saint-Simon in his relation to the policy of laissez-faire, 642.—Neither Saint-Simon nor the Saint-Simonians were socialists, 648.—III. The philosophy of history, 650.—The principle of productivity and its importance, 651.—IV. The rule of law and the harmony of interests in a society of producers, 657.—V. The Saint-Simonian criticism of competition, 665.—The division between the idle and the producing class, 668.—The rationalisation of economic enterprise, 674.—VI. The position and importance of the banks, 675.—The theory and rational use of credit, 677.—VII. Conclusion, 680.